(untitled) (Colombia Medica, 2009)
Introduction: The diseases that are partly or wholly determined by genetic factors, gradually assume a ratio of greater importance in the epidemiological profile of the child population, becoming one of the leading causes of mortality and morbidity. The perception of mothers of children affected by major congenital malformations has not been studied before in relation to the health system in Colombia. Objectives: To know the mother’s perceptions of children with congenital malformations, on the etiology of the disease for their children, medical care received and the potential consequences of the malformation. Methods: Qualitative exploratory descriptive study of focus groups with mothers of children suffering from major congenital malformations. Results: Mothers identified the problems of child care in relation to the health system, treatment ambivalent and prejudice of health personnel and the need for clear answers on the future of children, as well as the need for reforms in the health care of people affected.